PENGARUH MEDIA SOSIAL ONLINE DAN MEDIA PROMOSI OFFLINE TERHADAP PEMILIHAN MEREK PRODUK SKINCARE DAN KLINIK KECANTIKAN - Kussudyarsana, Kussudyarsana; Rejeki, Lestari (Universitas Muhammadiyah Surakarta, 2020)
This study aims to determine the effect of online social media and offline promotional media on the selection of skincare product brands and beauty clinics. The data used in this study were primary data and sample selection in this study uses a non-probability sampling approach with purposive sampling technique. The sample used was 300 respondents. Data analysis methods in this study include validity test, reliability test, classic assumption test, multiple linear regression test, hypothesis test. The results of this study indicate that (1) online social media has a significant effect on the selection of skincare product brands (2) online social media has a significant effect on beauty clinic selection (3) offline promotional media has a significant effect on skincare product brand selection (4) offline promotional media influences significant to the selection of beauty clinics (5) online social media is more effective than offline promotion media on the selection of skincare products and beauty clinics.Â